2022
DOI: 10.7759/cureus.23142
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Smear Layer Removal in Apical Third Using Four Different Irrigants With Ultrasonic Agitation: An In Vitro Scanning Electron Microscopy (SEM) Analysis

Abstract: This study aims to compare and evaluate the efficacy of four different irrigating solutions like sodium hypochlorite, ethylenediaminetetraacetic (EDTA), Oxum, and ozonated water with ultrasonic agitation in removing the smear layer in the apical third of root canals using Scanning Electron Microscopy (SEM). Materials and methodsFor the study, 50 freshly extracted human mandibular premolars with single well-developed roots without any curvatures were taken. The teeth taken were decoronated to obtain a uniform w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Its biocompatibility with human tissues has also been observed (Mohammed and Selivany, 2021;Kebede et al, 2021). The study also found that chamomile was more effective than NaOCl alone in removing smear layers than NaOCl + EDTA (Murugesan et al, 2022). The research findings indicate that Tea Tree Oil (TTO) could serve as a viable root canal irrigant for young patients, exhibiting antimicrobial properties similar to Chlorhexidine (CHX).…”
Section: Discussionmentioning
confidence: 69%
“…Its biocompatibility with human tissues has also been observed (Mohammed and Selivany, 2021;Kebede et al, 2021). The study also found that chamomile was more effective than NaOCl alone in removing smear layers than NaOCl + EDTA (Murugesan et al, 2022). The research findings indicate that Tea Tree Oil (TTO) could serve as a viable root canal irrigant for young patients, exhibiting antimicrobial properties similar to Chlorhexidine (CHX).…”
Section: Discussionmentioning
confidence: 69%
“…Twenty‐four reports investigated either the detrimental effects (20) or the regenerative potential (4) of EOW on oral hard and soft tissues (Table 3, Table S1). Most (16) were in vitro studies assessing potential endodontic applications 80,99,129–142 . Others examined dentine microhardness (human 134,136,137,143 ; bovine 144 ), dentine surface roughness (human 137 ), dentine structure (bovine 145 ), pulp/apical papilla cytotoxicity (human 67,146 ) and pulp dissolution capability (bovine 86,147,148 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most (16) were in vitro studies assessing potential endodontic applications. 80,99,[129][130][131][132][133][134][135][136][137][138][139][140][141][142] Others examined dentine microhardness (human 134,136,137,143 ; bovine 144 ), dentine surface roughness (human 137 ), dentine structure (bovine 145 ), pulp/apical papilla cytotoxicity (human 67,146 ) and pulp dissolution capability (bovine 86,147,148 ).…”
Section: Effects Of Eow On Oral Hard and Soft Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple investigative studies that utilized scanning electron microscopy (SEM) have shown the efficacy of sodium hypochlorite (NaOCl) irrigation in debris removal [ 4 ]. However, one should note that there is a significant disadvantage associated with NaOCl: its potential cytotoxic effects when inadvertently injected into peri-radicular tissue.…”
Section: Introductionmentioning
confidence: 99%